OPTIMALISASI KARAKTERISTIK NATA DE BANANA SKIN MELALUI PERUBAHAN KONSENTRASI ACETOBACTER XYLINUM - Marlinda Marlinda; Rita Hartati (Jurnal Optimalisasi, 2019)
This research aimed to determine the optimum concentration of Acetobacter xylinum to produce maximum nata de banana skin. The banana peel was used as a medium with Acetobacter xylinum added with concentrations of 10%, 20%, 30%, 40% of 400 ml of media solution. The results showed that the thickness of nata de banana skin with treatment variation were 0.77cm, 2.09cm, 2.77cm, 2.38cm, yield of 22.6%, 42.3%, 51.4%, 46.4%, and water content 87,6%, 86,6% 85,8% 86,2%. The preferred organoleptic test is at 30% concentration in the form of color, taste and suppleness. The result of research can be concluded that Acetobacter xylinum optimum concentration to produce the maximum of nata de banana skin is 30% for thickness, rendement, moisture content and organoleptic test of nata de banana skin.